Vegetation vs. Anoxic Controls on Degradation of Plant Litter in a Restored Wetland - Hernes, Peter J.; Miller, Robin L.; Dyda, Rachael Y.; Bergamaschi, Brian A. (Frontiers in Environmental Science, 2020)
The ability of wetlands to accrete organic matter in response to rising sea-level is a key to landscape resilience, especially in light of reduced sediment availability consequent to dam construction and channelization. This study examined degradation of cattail (Typha spp) and tule (Schoenoplectus acutus) litters in restored wetlands through the lens of lignin, a major structural biopolymer in vascular plants with degradation characteristics very sensitive to oxic vs. anoxic conditions. A series of litterbags were deployed during the first 10 years after flooding of Deep (55 cm) and Shallow (25 cm) restored wetlands. As emergent marsh vegetation spread through the maturing wetlands, anoxic conditions were more prevalent and overall degradation rates of litter in litterbags were lower. In later experiments in the maturing wetlands, lignin was progressively enriched in litter as evidenced by carbon-normalized yields (8) that increased in tule starting materials from 6.3 to 7.1 mg 100mgOC-1 to as high as 9.9 mg 100mgOC-1, and in cattail starting materials from 5.9 to 7.0 mg 100mgOC-1 to as high as 10.9 mg 100mgOC-1. However, in an experiment initiated soon after the restored wetlands were constructed, 8 in tule litter decreased from 6.8 to 3.6 mg 100mgOC-1, highlighting the prevalence of initial oxic conditions. With the exception of the early oxic conditions for tule there was an overall trend of decreasing lignin acid-to-aldehyde ratios with litter degradation, which runs counter to most studies in the literature. We hypothesize that this reflects the utilization of more oxygen-rich lignin components as electron acceptors in redox reactions. No consistent differences were observed in degradation patterns between the Shallow and Deep wetlands. There were distinct differences in lignin degradation in cattail (more resistant) vs. tule (less resistant), which indicates that although anoxia may be the dominant control on organic matter accretion in wetlands, specific types of vegetation in restored or constructed wetlands affects organic matter preservation, and hence accretion. Thus, selective management of predominant species in wetlands may prove important for the ability of wetlands to maintain emergent vegetation during sea-level rise and to preserve the overall stability of wetland soils.